In vitro and in vivo effects of a novel bioactive glass‐based cement used as a direct pulp capping agent. Issue 1 (25th March 2018) - Hanada, Kaori; Morotomi, Takahiko; Washio, Ayako; Yada, Naomi; Matsuo, Kou; Teshima, Hiroki; Yokota, Kazuyoshi; Kitamura, Chiaki
Abstract: Direct pulp capping is an important procedure for preserving pulp viability. The pulp capping agent must possess several properties, including usability, biocompatibility, and the ability to induce reparative dentin formation. In this study, a novel bioactive glass‐based cement was examined to determine whether the cement has the necessary properties to act as a direct pulp capping agent. Physicochemical properties of the bioactive glass‐based cement and in vitro effects of the cement on odontoblast‐like cells, as well as in vivo effects on the exposed dental pulp, were analyzed. The cement immersed in water stabilized at pH10, and hydroxyapatite‐like precipitation was induced on the surface of the cement in simulate body fluid. There were no cytotoxic effects on the viability, alkaline phosphatase activity, or calcium deposition ability of odontoblast‐like cells. In the in vivo rat study of an exposed dental pulp model, the cement induced a sufficient level of reparative dentin formation by odontoblast‐like cells expressing odontoblastic markers at the exposed area of the dental pulp. These results suggest that the newly developed bioactive glass‐based cement provides favorable biocompatibility with the dental pulp and may be useful as a direct pulp capping agent. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 161–168, 2019.